Mathematics Learning Media Development Using Realistic Mathematics Education - Sugianto, Sugianto; Roza, Yenita; Maimunah , Maimunah (FKIP-Universitas Riau, 2020)
This research aims to develop learning mathematics media using proven validity-PMR approach, practicality and effectiveness in improving HOTS of Junior High School students class VIII. This type of research was the development of ADDIE model consisting of analysis, design, development, implementation and evaluation. The tests were carried out in four phases, expert test, limited test, field test, and effectiveness test. The subjects in this study were teachers and students. The instruments used were validation sheet, student’s questionnarie, observation sheet and instrument test. The results show the learning media developed has fulfilled validity, practicality and effectiveness aspect. (1) The validity result shows the developed learning media in the category very valid with the average value on syllabus 3.81. While the learning plane (RPP) is 3.62, and student worksheet (LKPD) is 3.51, and test instrument is 3.45. (2) Limited test results shows the developed mathematical learning media in very practical category with score of 3.41. (3) Field test result shows the learning media developed is very practical, on teacher learning implementation observation sheet 3.62, on the student’s questionnaire 3.44. Finally, the developed learning media can be ready to use in the school.